'SKILLS FOR GROWING UP': SUPPORTING AUTONOMY IN YOUNG PEOPLE WITH KIDNEY DISEASE. Issue 2 (23rd December 2013) - Sattoe, Jane N.T.; Hilberink, Sander R.; Peeters, Mariëlle A.C.; van Staa, AnneLoes
SUMMARY Background and Objectives End‐stage kidney disease (ESKD) may interfere with children's developmental task of acquiring autonomy and participation. The Skills for Growing Up tool encourages normal development towards independence and autonomy during paediatric rehabilitation. This study aimed to adapt this self‐management tool for use in paediatric nephrology, and to test whether its use is feasible in daily practice. Design and Participants A Delphi study was conducted among patients, their parents, professionals and experts to adjust the tool for use in nephrology. Feasibility was studied through individual and group interviews with professionals in all Dutch paediatric nephrology centres. Results Agreement was reached on the areas of social participation and medical management of ESKD. Compared with the original, the new instrument holds considerable more attention for autonomy in the renal healthcare area; for example, dealing with medication and transplantation. Professionals used and appreciated the tool, but the paper form was seen to limit feasibility. Conclusions Making the tool available online is important. The challenge for professionals is to move beyond the focus on medical management and to consider developmental tasks when coaching their patients into adulthood. Application to Practice The Skills for Growing Up—Nephrology (SGU‐N) tool is a promising instrument for use by professionals in paediatric nephrology. Its use can help young people achieving autonomy and may contribute to their successful transition to adulthood and adult care.